Microlearning in Teacher Competence Development: A Bibliometric Analysis - Hutagalung, Johanna Cristy; Johan, Riche Cynthia (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
In an era where digital learning and teacher adaptability are reshaping education, understanding the role of microlearning in teacher competence development is increasingly essential. This bibliometric study maps global research on microlearning from 2019 to 2025, analyzing 54 documents indexed in Scopus using VOSviewer and descriptive statistics. The analysis identifies six core themes: (1) digital learning infrastructure, (2) medical education, (3) learner motivation, (4) assessment strategies, (5) teaching approaches, and (6) contextual innovations through social media. Cluster 1 highlights technology in microlearning, focusing on e-learning and mobile platforms, while Cluster 3 emphasizes learner engagement and affective learning. Two key insights emerge. First, digital technology, especially mobile-based learning, has become central to the microlearning ecosystem. Second, the COVID-19 pandemic has accelerated its adoption, making it a flexible solution for remote teacher development. Theoretically, this study contributes by mapping the intellectual structure of microlearning and identifying gaps, such as teachers' social and personality competencies, that remain underexplored in the current literature. In practice, it provides policymakers with actionable insights for integrating microlearning into professional development programs, especially in regions with limited access to formal training resources. Despite fragmentation in collaboration networks, the findings reveal opportunities to enhance interdisciplinary and international research partnerships. Future research should focus on applying microlearning to develop teachers' social and personality competencies, areas crucial for effective teaching but often overlooked.